ANALISIS KUALITAS PELAYANAN, KEPERCAYAAN SERTA CITRA KOPERASI TERHADAP KEPUASAN DAN LOYALITAS ANGGOTA - Sutrisno, Sutrisno; Cahyono, Dwi; Qomariah, Nurul (Universitas Muhammadiyah Jember, 2017)
ABSTRACTThe purpose of this study is to analyze the influence of service quality, trust, image of cooperative to the satisfaction and loyalty of members. Quantitative descriptive research type with explanatory research design. The population in this study is all members of Koprimka